PENGARUH PENGGUNAAN CHATGPT TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS X DALAM PEMBELAJARAN INFORMATIKA DI SMA KRISTEN CITRA BANGSA MANDIRI KUPANG - Mardiana Teku Nuwa; Maria Magdalena Beatrice Sogen; Jhon Enstein (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mardiana Teku Nuwa. The Effect of Using ChatGPT on the Critical Thinking Skills of Tenth-Grade Students in Informatics Learning at SMA Kristen Citra Bangsa Mandiri Kupang. Study Program of Informatics Education, Faculty of Teacher Training and Education, Citra Bangsa University, Kupang.Advisors: Mr. Jhon Enstein, S.Kom.,M.Cs and Dr. Maria M. B. Sogen, S.Kom., M.Pd. This study examines the influence of ChatGPT on the critical thinking skills of Grade X students in Informatics learning at SMA Kristen Citra Bangsa Mandiri Kupang. Using a quantitative quasi-experimental design, the research involved an experimental class using ChatGPT and a control class receiving conventional instruction. Findings show significant improvements in learning outcomes and critical thinking indicators in the experimental group. These results suggest that ChatGPT enhances reflective, analytical, and independent learning. The study emphasizes the importance of digital literacy and ethics to ensure that ChatGPT is used as a thinking tool rather than merely a source of answers effectively.